Pengaruh Penerapan Sistem E-Filing Terhadap Kepatuhan Wajib Pajak Orang Pribadi Dengan Pemahaman Internet Sebagai Variabel Moderasi (Studi Pada Wajib Pajak Orang Pribadi di KPP Pratama Sumbawa Besar) - Istutik Istutik; Dwi Suci Pertiwi (INSPIRASI : JURNAL ILMU-ILMU SOSIAL, 2022)
Taxpayer compliance is a very important key to increasing state revenue from the tax sector. This study aims to examine the effect of the application of the e-filing system on taxpayer compliance with the understanding of the internet as a moderator. The research was conducted on individual taxpayers registered at KPP Pratama Sumbawa Besar. This research is quantitative research with hypothesis testing which will be analyzed using Moderated Regression Analysis (MRA). By using probability sampling as a sampling technique, the number of respondents in this study was 200 people. The results showed that the application of the e-filing system had a positive effect on taxpayer compliance. Then the understanding of the internet moderates or strengthens the relationship between the application of the e-filing system to taxpayer compliance.